2019
DOI: 10.1038/s41380-019-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural changes in cannabis dependence: association with MAGL

Abstract: Cannabis use is rising, yet there is poor understanding of biological processes that might link chronic cannabis use to brain structural abnormalities. To lend insight into this topic, we examined white matter microstructural integrity and gray matter cortical thickness/density differences between 89 individuals with cannabis dependence (CD) and 89 matched controls (64 males, 25 females in each group) from the Human Connectome Project. We tested whether cortical patterns for expression of genes relevant for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 74 publications
1
36
1
Order By: Relevance
“…However, a few recent large studies did find morphometric differences in association with cannabis use. ; Although the literature is consistent in reporting lower structural connectivity in participants with CUD (Arnone et al, 2008;Ashtari et al, 2009;Becker et al, 2015;Epstein & Kumra, 2015;Gruber et al, 2014;Jacobus et al, 2009;Jakabek et al, 2016;Manza et al, 2019;Murray et al, 2017;Orr et al, 2016;Shollenbarger et al, 2015;Zalesky et al, 2012), we did not find conclusive evidence for lower FA in the CUD group (0.3 < BF < 3). Functional connectivity studies, however, are more inconsistent.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…However, a few recent large studies did find morphometric differences in association with cannabis use. ; Although the literature is consistent in reporting lower structural connectivity in participants with CUD (Arnone et al, 2008;Ashtari et al, 2009;Becker et al, 2015;Epstein & Kumra, 2015;Gruber et al, 2014;Jacobus et al, 2009;Jakabek et al, 2016;Manza et al, 2019;Murray et al, 2017;Orr et al, 2016;Shollenbarger et al, 2015;Zalesky et al, 2012), we did not find conclusive evidence for lower FA in the CUD group (0.3 < BF < 3). Functional connectivity studies, however, are more inconsistent.…”
Section: Discussioncontrasting
confidence: 97%
“…Nevertheless, a smaller hippocampal volume has been associated with current cannabis dependence (Chye et al, 2019), and tetrahydrocannabinol (THC, a psychoactive component of cannabis) positive urine but not lifetime use (Owens, Sweet, & MacKillop, 2020). In contrast, white matter integrity, as inferred from fractional anisotropy (FA) derived from diffusion tensor imaging (DTI) may be reduced in cannabis users (Arnone et al, 2008; Becker, Collins, Lim, Muetzel, & Luciana, 2015; Epstein & Kumra, 2015; Gruber, Dahlgren, Sagar, Gönenç, & Lukas, 2014; Jacobus, Squeglia, Bava, & Tapert, 2013; Jakabek, Yücel, Lorenzetti, & Solowij, 2016; Manza, Yuan, Shokri‐Kojori, Tomasi, & Volkow, 2019; Murray et al, 2017; J. M. Orr et al, 2016; Shollenbarger, Price, Wieser, & Lisdahl, 2015), even after months of abstinence (Ashtari, Cervellione, Cottone, Ardekani, & Kumra, 2009). Although many studies have looked at functional connectivity and cannabis use, most studies involve activation tasks and/or region of interest approach (Blest‐Hopley, Giampietro, & Bhattacharyya, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Findings have been inconsistent, with some studies finding substantially smaller subcortical volumes in chronic cannabis users compared to controls ( 16 18 ), whereas others have reported that after controlling for key confounding variables like tobacco usage, these differences are virtually non-existent ( 19 , 20 ). We and others have argued that these discrepant findings are due to generally small sample sizes and inadequate matching on control groups ( 21 ). Nevertheless, several recent reviews have been devoted to the topic ( 22 24 ) and some consensus seems to have emerged that cerebellum, amygdala, and hippocampus volumes appear to be most consistently affected by chronic cannabis use across studies ( 8 ).…”
Section: Introductionmentioning
confidence: 93%
“…An extensive number of studies have pointed out some similarities in the mode of action of the molecules that modulate oligodendrogenesis during postnatal development and in the adult CNS (Itoh, Maki, Lok, & Arai, 2015;Patel & Klein, 2011). Indeed, chronic cannabis use has been associated with structural differences in the gray matter, but more prominently in white matter tracts (Manza, Yuan, Shokri-Kojori, Tomasi, & Volkow, 2019;Orr, Paschall, & Banich, 2016), with greater functional connectivity in orbitofrontal cortex network and increased structural connectivity of the forceps minor of cannabis users, which in turn has been suggested to reflect better myelination and/or intact axons (Filbey et al, 2014;Song et al, 2002). Therefore, the identification in this study of THC as a potent inductor of OPC differentiation in vivo opens the possibility that this molecule could potentially modulate CNS myelination in the adult human brain.…”
Section: Discussionmentioning
confidence: 99%